Pengembangan Lagu Kreasi dalam Meningkatkan Bahasa Anak Usia Dini di TK Islam Darul Falah Padang Panjang - Khairi, Miftahul; Kardi, Juliwis; Citra Dewi, Ayu; Intan Wahyuni, Sri; Cahya Dwi Lestari, Mega; Fitria, Yenni (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2024)
This research is based on the problem found at Darul Falah Islamic Kindergarten in Padang Panjang which is the lack of learning medium support in enhancing the language skills of early childhood students. To address this issue the researcher developed creative songs. This study aims to improve early childhood language skills through the development of creative song media at TK Islam Darul Falah Padang Panjang. The research method used is Research and Development (R&D) with the 4-D development model: define, design, develop, and disseminate. The research subjects are early childhood learners, and the object is the creative song media. Data collection techniques include observation, interviews, and documentation, while the data analysis technique uses descriptive quantitative analysis. The validation results by the material expert showed an eligibility rate of 88%, and the media expert validation reached 96.36%, both categorized as highly feasible. Field trials showed an average score of 83.53% with children's language development categorized as developing very well. The conclusion of this research is that the creative songs are highly feasible and effective as learning media to improve early childhood language skills